Deleuze and Music - Buchanan, Ian; Swiboda, Marcel (Edinburgh Edinburgh University Press, 2004)
The first volume to explore Deleuze's ideas from the perspective of music and sound.
Introduction: Deleuze and Music / Ian Buchanan -- Studies in Applied Nomadology: Jazz Improvisation and Post-Capitalist Markers / Eugene Holland -- Is Pop Music? / Greg Hainge -- Deleuze, Adorno, and the Composition of Musical Multiplicity / Nick Nesbitt -- Affect and Individuation in Popular Electronic Music / Drew Hemment -- Violence in Three Shades of Metal: Death, Doom and Black / Ronald Bogue -- Becoming-Music: The Rhizomatic Moment of Improvisation / Jeremy Gilbert -- Rhythm: Assemblage and Event / Phil Turetsky -- What I Hear is Thinking Too: The Deleuze Tribute Recordings / Timothy S. Murphy -- Music and the Social-Historical Real: Rhythm, Series and Critique in Deleuze and O. Revault d'Allonnes / Jean-Godefroy Bidima -- Cosmic Strategies: The Electric Experimebts of Miles Daves / Marcel Swiboda
Includes an index and contributors' bios
Keywords: Deleuze, Gilles -- 1925-1995; Adorno, Theodor W. -- 1903-1969; Davis, Miles -- 1926-1991; 20th Century (1901-2000); Music philosophy and esthetics; Jazz; Improvisation; Popular music; Electronic music; Rhythm; Assemblage